Episodic replacement of clotting factor concentrates does not prevent bleeding or musculoskeletal damage – the MUSFIH study. Issue 4 (2nd June 2017) - Poonnoose, P.; Carneiro, J. D. A.; Cruickshank, A. L.; El Ekiaby, M.; Perez Bianco, R. P.; Ozelo, M. C.; De Bosch, N.; Baghaipour, M.; Tien, S. L.; Chuansumrit, A.; D'Amico, E. A.; van Zyl, A.; et al.
Abstract : Patients and methods: A longitudinal study was carried out in 255 children from 10 centres in nine developing countries over 5 years to assess the musculoskeletal outcome of children on episodic factor replacement. Outcome was documented by assessment of the annual joint bleeding rate (AJBR), WFH clinical and Pettersson radiological joint scores as well as the FISH score for activities. Of the 203 patients for whom data was available at the end of 5 years, 164 who had received only episodic treatment are included in this report. Results: The median age at the beginning of the study was 10 years (IQR 7–12). The median clotting factor concentrate (CFC) usage was 662 IU kg −1 year −1 (IQ range: 280–1437). The median AJBR was 10 (IQ range: 5–17). The median AJBR was higher in the older children with the median being 5 for the 5 year old child, while it was 9 for the 10 year old and 11 for children older than 15. Given the episodic nature of the replacement therapy, those with a higher AJBR used significantly greater annual CFC doses ( P < 0.001); The median change in WFH clinical score and Pettersson radiological score over the 5 years was 0.4/year for each, while the FISH deteriorated at a rate of 0.2/year with poor correlation of these changes with CFC dose. WFH and FISH scores were significantly worse in those with an AJBR of >3 per year ( P = 0.001). The change in the Pettersson score was significantly more in those with an AJBR of >5 per year ( P = 0.020). Significant changes in FISH scores were only noted after 10 years of age. Conclusion: Episodic CFC replacement over a large range of doses does not alter the natural course of bleeding in haemophilia or the musculoskeletal deterioration and should not be recommended as a long term option for treatment. Prophylaxis is the only way to preserve musculoskeletal function in haemophilia.